Development of a TaqMan Multiplex Real Time PCR assay for the detection of Trypanosoma cruzi in blood samples of wild and domestic animals - Wehrendt, Diana Patricia (2017)
Chagas disease affects about 7 million people worldwide and is caused by the protozoan parasite Trypanosoma cruzi. In the argentine Chaco, an endemic area of Chagas disease, little is known about T. cruzi domestic and wild transmission cycles. Therefore, a field trial in rural areas near Añatuya, Santiago del Estero, for eco-epidemiological purposes, is under way. Due to the large number of samples we estimate to obtain in the trial, our goal was to develop a TaqMan multiplex PCR assay that simultaneously allowed T. cruzi detection and DNA integrity control. To achieve this, we choose the interphotoreceptor retinoid-binding protein (IRBP) gene, because it is highly conserved in all mammals and its use as a DNA integrity control in a conventional PCR was previously described. Based on an IRBP sequence alignment of several domestic and wild species, we designed a TaqMan probe to a highly conserved region within the amplified zone. The detection of satellite T. cruzi DNA was performed with the primers and probe already developed in our laboratory. Once the parameters for the multiplex PCR were established, the assay was tested in a total of 45 blood samples of wild mammals. So far, all samples analyzed were T. cruzi undetectable. Our DNA integrity control worked well for Conepatus chinga, Molossus sp, Lagostomus maximus, Lycalopex gymnocercus, Rattus rattus, Calomys sp, Galea musteloides and Leopardus geoffroyi. However, it did not work for Chaetophractus villosus, Tolypeutes matacus, Graomys chacoensis and Myotis sp. DNA integrity was tested by amplification of beta-actin in these cases. A sequence analysis to identify mutations that prevent amplification of the selected IRBP region in these species will be done. The performance of the multiplex PCR in domestic animal samples remains to be studied.